Influence of Dimethyl Sulfoxide as a Penetration Enhancer of Piroxicam Gel Through Biological Skin: Effect of DMSO on piroxicam penetration from skin - Moghbel, Abdolhossein; Faghiri, Asghar (Iranian Journal of Pharmaceutical Sciences, 2006)
Piroxicam is a non-steroidal anti-inflammatory agent which has an extensive use in rheumatic disorders. Since its skin penetration is still a subject for research, the aim of this study was to evaluate the effect of dimethyl sulfoxide on percutaneous penetration of piroxicam gel formulation through skin. In this study, as a model, two types of 0.5% piroxicam new gels, so called red and green gel, were prepared using 5% (w/w) DMSO only for the red gel. Water, ethanol and propylene glycol were the solvent composition specified by a triple phase diagram, in addition to carbomer P934 and hydroxypropyl methylcellulose as the gel bases. The release and dermal penetration of the drug were measured and compared with a commercial brand using static diffusion cells and hairless rat skin as a biological membrane, by UV spectrophotometer. Also, piroxicam serum level was measured after application of 1 g gel on the deltoid muscle, twice daily for two weeks, in three groups of healthy male volunteers. The results of all physico-chemical controls for the gels indicated an acceptable criteria. The penetration of piroxicam through animal skin showed a good linearity between the square root of time and amount of piroxicam released from the gels. The in vitro study showed that application of DMSO had no significant effect on percutaneous penetration of the drug through animal skin. In human study, the red gel containing DMSO had the highest piroxicam serum level with a relatively meaningful difference between the results compare to the green and commercial gels (p<0.05). But the green and commercial gels had no statistical difference. This preference might be related to the in vivo DMSO positive effect as a penetration enhancer, contrary to the in vitro results. Therefore, relying on laboratorial data is not always sufficient.